2018
DOI: 10.1007/s00101-018-0476-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematische Analyse von Atemwegsregistern in der Notfallmedizin

Abstract: This study identified eleven EARs that sometimes widely differed concerning inclusion periods, inclusion criteria, definition of complications and application of newer methods of emergency airway management. Thus, comparability of the reported results and first-pass success rates is only possible to a limited extent. The authors therefore advocate the initiation of an airway registry in emergency medicine in German-speaking countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Due to the fact that in Germany a multi-centre airway registry does not exist, we suggest that this should be initiated in order to analyse the situation countrywide. Studies identified more than eleven emergency airway registries that sometimes widely differed concerning inclusion period, inclusion criteria, definition of complications and application of newer methods of emergency airway management [47]. Comparability of the reported results and first-pass-success rates is only possible to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that in Germany a multi-centre airway registry does not exist, we suggest that this should be initiated in order to analyse the situation countrywide. Studies identified more than eleven emergency airway registries that sometimes widely differed concerning inclusion period, inclusion criteria, definition of complications and application of newer methods of emergency airway management [47]. Comparability of the reported results and first-pass-success rates is only possible to a limited extent.…”
Section: Discussionmentioning
confidence: 99%